A comparative study on the joint coordination of archery athletes of different skill levels: Based on functional data analysis - Zhang, B.; Lin, Z.-C. (Quality in Sport, 2024)
Purpose: Joint coordination is a critical factor influencing high-quality technical movements. By analyzing the changes between joints through functional data analysis, characteristic parameters can be derived. This study employs functional data analysis to explore the differences in joint coordination characteristics among archery athletes at various skill levels, offering a new perspective for coaches and athletes to analyze specific movement techniques.